2016
DOI: 10.1001/jamacardio.2016.2860
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Outcomes of Coronary Angiography and Percutaneous Coronary Intervention After Out-of-Hospital Cardiac Arrest Associated With Ventricular Fibrillation or Pulseless Ventricular Tachycardia

Abstract: Coronary angiography, PCI, and survival to discharge have increased in VT/VF OHCA survivors from event to hospitalization. However, a significant proportion of patients with VT/VF OHCA, especially those without STE, do not undergo coronary angiography and revascularization. Prospective studies are needed to determine whether this limitation has a survival effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 38 publications
6
51
0
1
Order By: Relevance
“…Inquiring into the management of CAD in patients resuscitated from a SCA, Patel et al analyzed temporal trends in the use of CC and PCI. They found that in the group of patients hospitalized after out‐of‐hospital SCA caused by shockable rhythms without ST elevation, PCI was performed in almost one third of the patients . In our cohort, 18.4% of patients were treated with PCI (21.6% among those with shockable initial rhythm).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Inquiring into the management of CAD in patients resuscitated from a SCA, Patel et al analyzed temporal trends in the use of CC and PCI. They found that in the group of patients hospitalized after out‐of‐hospital SCA caused by shockable rhythms without ST elevation, PCI was performed in almost one third of the patients . In our cohort, 18.4% of patients were treated with PCI (21.6% among those with shockable initial rhythm).…”
Section: Discussionmentioning
confidence: 70%
“…Thus, Kaplan-Meier's curves including ≥50 DS% did not show was performed in almost one third of the patients. 23 In our cohort, 18.4% of patients were treated with PCI (21.6% among those with shockable initial rhythm). Although we did not specifically evaluate the effect of revascularization over prognosis, those patients with the highest burden of CAD (three vessel disease with DS% ≥70), could benefit from a revascularization as complete as possible to reduce mortality.…”
Section: Discussionmentioning
confidence: 80%
“…This resulted in a cohort of 151,628 hospitalizations which comprise our study sample. Ventricular tachycardia and VF were identified by the ICD‐9CM code 427.1 OR 427.41 . These codes have shown a positive predictive value of 82% .…”
Section: Methodsmentioning
confidence: 99%
“…Ventricular tachycardia and VF were identified by the ICD-9CM code 427.1 OR 427.41. 17 These codes have shown a positive predictive value of 82%. 18 Intraaortic balloon pump (IABP), percutaneous ventricular assist devices (PVADs), and extracorporeal membrane oxygenator (ECMO) were identified using the ICD-9CM codes 37.61, 37.68, and 39.65, respectively.…”
Section: Study Populationmentioning
confidence: 99%
“…Recently, Patel et al published data of more than 400,000 patients with ventricular tachycardia or ventricular fibrillation (VT/VF) OHCA from the Nationwide Inpatient Sample (NIS) database. The study reports on trends of the application of coronary angiography (CAG) and percutaneous coronary intervention (PCI), as well as outcome after OHCA (1). Evidence that CAG may reduce mortality in OHCA patients with and without ST-segment elevation (STE) myocardial infarction (STEMI) was obtained in several previous observational studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%